A survey of blockchain consensus algorithms performance evaluation criteria - Bamakan, Seyed Mojtaba Hosseini; Motavali, Amirhossein; Babaei Bondarti, Alireza (Expert systems with applications, 2020)
•A comprehensive review of the state-of-the-art blockchain consensus algorithms.•An analytical framework to evaluate the pros and cons of consensus mechanisms.•The comparison criteria are weighted by the pairwise comparison method.•The existing open issues, challenges and directions to enlighten future research. How to reach an agreement in a blockchain network is a complex and important task that is defined as a consensus problem and has wide applications in reality including distributed computing, load balancing, and transaction validation in blockchains. Over recent years, many studies have been done to cope with this problem. In this paper, a comparative and analytical review on the state-of-the-art blockchain consensus algorithms is presented to enlighten the strengths and constraints of each algorithm. Based on their inherent specifications, each algorithm has a different domain of applicability that yields to propose several performance criteria for the evaluation of these algorithms. To overview and provide a basis of comparison for further work in the field, a set of incommensurable and conflicting performance evaluation criteria is identified and weighted by the pairwise comparison method. These criteria are classified into four categories including algorithms’ throughput, the profitability of mining, degree of decentralization and consensus algorithms vulnerabilities and security issues. Based on the proposed framework, the pros and cons of consensus algorithms are systematically analyzed and compared in order to provide a deep understanding of the existing research challenges and clarify the future study directions.